2016
DOI: 10.1016/j.jcms.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Severe compromise of preosteoblasts in a surgical mouse model of bisphosphonate-associated osteonecrosis of the jaw

Abstract: Objectives: The effect of amino-bisphosphonates on osteoblastic lineage and its potential contribution to the pathogenesis of bisphosphonate-associated osteonecrosis of the jaw (BONJ) remain controversial. We assessed the effects of zoledronic acid (ZOL) on bone and vascular cells of the alveolar socket using a mouse model of BONJ. Material and methods: Thirty-two mice were treated twice a week with either 100 mu g/kg of ZOL or saline for 12 weeks. The first left maxillary molar was extracted at the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
2
3
0
6
Order By: Relevance
“…Consistent with the results of many other studies, the actions of ZOL (Exp + Saline group) were not restricted exclusively to osteoclasts in the present work (Basso et al, 2013;Córdova et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results of many other studies, the actions of ZOL (Exp + Saline group) were not restricted exclusively to osteoclasts in the present work (Basso et al, 2013;Córdova et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The majority of previous studies reported the use of ZA via IP (intraperitoneal) or IV (intravenous) administration as an antiresorptive medication of choice for inducing MRONJ lesions in mice [15,17,24,25,27,29,30,32,33,35,37,39,[42][43][44][45][46], considering its higher potency when compared to other IV or oral nBP's [47]. Moreover, all mouse studies presented in S1 Table were performed in young or adult animals (age varying from 6 to 16 weeks old).…”
Section: Introductionmentioning
confidence: 99%
“…Até o presente momento, a maioria dos estudos pré-clínicos que investigaram as alterações ósseas induzidas pelos BF em modelos animais, avaliaram as regiões dos alvéolos após a exodontia em modelos de OMAB (JABBOUR et al, 2014;CORDOVA et al, 2016).…”
Section: Lista De Ilustraçõesunclassified
“…Em concordância com os achados desta investigação, estudos anteriores demonstraram que a administração de AZ aumentou a densidade óssea na mandíbula (JABBOUR et al, 2014;CORDOVA et al, 2016). No entanto, esses estudos avaliaram o volume ósseo no alvéolo pós-extração de modelos animais de OMAB, onde o processo de reparo, a inflamação e a própria doença podem influenciar os resultados (JABBOUR et al, 2014;CORDOVA et al, 2016).…”
Section: Discussão Discussãounclassified
See 1 more Smart Citation